Limited window for donation of convalescent plasma with high live-virus neutralizing antibody titers for COVID-19 immunotherapy - Abhinay Gontu (Nature Portfolio, 2021)
Gontu et al. conducted a longitudinal study in COVID patients in which they assessed the response trajectories of antibodies directed to the SARS-CoV-2 surface spike glycoprotein and in vitro SARS-CoV-2 live virus neutralizing titers. Their measurements demonstrate the presence of an optimum window for convalescent plasma donation as well as predictions of the most suitable donor type.